(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2025)
Suicide is the leading cause of external death in our country. This makes it a serious public health problem, so it is essential to implement suicide prevention measures. Legal and forensic medicine plays an important role in the investigation of suicidal behaviour through the collection of statistics related to suicide and the performance of psychological autopsy. Sometimes it can be difficult to differentiate between suicide, accident or homicide. Assessing in the first place the concept of death, it is an unnatural death that always requires judicial investigation. In this sense, suicide is a classic theme of legal medicine. It is a very complex issue, in which there are multiple approaches, which means that it has ceased to be a mostly medical-legal issue, to be shared by multiple professionals.